The Role of Lamins in the Nucleoplasmic Reticulum, a Pleiomorphic Organelle That Enhances Nucleo-Cytoplasmic Interplay - Stiekema, Merel; Houben, Frederik; Verheyen, Fons; Borgers, Marcel; Menzel, Julia; Meschkat, Martin; van Zandvoort, Marc A. M. J.; Ramaekers, Frans C. S.; Broers, Jos L. V. (Frontiers in Cell and Developmental Biology, 2022)
Invaginations of the nuclear membrane occur in different shapes, sizes, and compositions. Part of these pleiomorphic invaginations make up the nucleoplasmic reticulum (NR), while others are merely nuclear folds. We define the NR as tubular invaginations consisting of either both the inner and outer nuclear membrane, or only the inner nuclear membrane. Specifically, invaginations of both the inner and outer nuclear membrane are also called type II NR, while those of only the inner nuclear membrane are defined as type I NR. The formation and structure of the NR is determined by proteins associated to the nuclear membrane, which induce a high membrane curvature leading to tubular invaginations. Here we review and discuss the current knowledge of nuclear invaginations and the NR in particular. An increase in tubular invaginations of the nuclear envelope is associated with several pathologies, such as laminopathies, cancer, (reversible) heart failure, and Alzheimer’s disease. Furthermore, viruses can induce both type I and II NR. In laminopathies, the amount of A-type lamins throughout the nucleus is generally decreased or the organization of lamins or lamin-associated proteins is disturbed. Also, lamin overexpression or modulation of lamin farnesylation status impacts NR formation, confirming the importance of lamin processing in NR formation. Virus infections reorganize the nuclear lamina via (de)phosphorylation of lamins, leading to an uneven thickness of the nuclear lamina and in turn lobulation of the nuclear membrane and the formation of invaginations of the inner nuclear membrane. Since most studies on the NR have been performed with cell cultures, we present additional proof for the existence of these structures in vivo, focusing on a variety of differentiated cardiovascular and hematopoietic cells. Furthermore, we substantiate the knowledge of the lamin composition of the NR by super-resolution images of the lamin A/C and B1 organization. Finally, we further highlight the essential role of lamins in NR formation by demonstrating that (over)expression of lamins can induce aberrant NR structures.